2020
DOI: 10.1186/s12931-020-01582-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum surfactant protein D as a predictive biomarker for the efficacy of pirfenidone in patients with idiopathic pulmonary fibrosis: a post-hoc analysis of the phase 3 trial in Japan

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal disorder with a variable disease course. The recent advancement of antifibrotic therapy has increased the need for reliable and specific biomarkers. This study aimed to assess alveolar epithelial biomarkers as predictors for the efficacy of the antifibrotic drug pirfenidone. Methods We conducted a post-hoc analysis of the prospective, multicenter, randomized, placebo-controlled, phase 3 trial of pirfenidone in Japan (total, n = 267; pirfen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…Moreover, in this group, the short-term changes in KL-6 levels correlated with FVC changes over 6 months. Few recent studies have studied biomarkers for predicting treatment response in patients with IPF receiving antifibrotic agents [12,13]. Ikeda et al, in the post-hoc analysis of the phase 3 trial of pirfenidone in Japan, showed that baseline serum surfactant protein D level (OR, 1.003; 95% CI 1.000-1.006, p = 0.028) predicted DP (≥ 10% relative decline in FVC from baseline and/or death over 1 year after treatment) in the pirfenidone group (n = 163) in the multivariate logistic analysis adjusted for smoking, BMI, FVC and alveolar-arterial oxygen difference [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in this group, the short-term changes in KL-6 levels correlated with FVC changes over 6 months. Few recent studies have studied biomarkers for predicting treatment response in patients with IPF receiving antifibrotic agents [12,13]. Ikeda et al, in the post-hoc analysis of the phase 3 trial of pirfenidone in Japan, showed that baseline serum surfactant protein D level (OR, 1.003; 95% CI 1.000-1.006, p = 0.028) predicted DP (≥ 10% relative decline in FVC from baseline and/or death over 1 year after treatment) in the pirfenidone group (n = 163) in the multivariate logistic analysis adjusted for smoking, BMI, FVC and alveolar-arterial oxygen difference [12].…”
Section: Discussionmentioning
confidence: 99%
“…Few recent studies have studied biomarkers for predicting treatment response in patients with IPF receiving antifibrotic agents [12,13]. Ikeda et al, in the post-hoc analysis of the phase 3 trial of pirfenidone in Japan, showed that baseline serum surfactant protein D level (OR, 1.003; 95% CI 1.000-1.006, p = 0.028) predicted DP (≥ 10% relative decline in FVC from baseline and/or death over 1 year after treatment) in the pirfenidone group (n = 163) in the multivariate logistic analysis adjusted for smoking, BMI, FVC and alveolar-arterial oxygen difference [12]. Neighbors et al, in a post-hoc assessment of the CAPACITY (n = 184) and ASCEND (n = 229) trials, also investigated the association between the levels of various biomarkers (CCL13, CCL17, CCL18, CXCL13, CXCL14, COMP, interleukin 13, MMP3, MMP7, osteopontin, periostin, and YKL40) and absolute decline in FVC (%) over 12 months in patients with IPF treated with pirfenidone; however, they were unable to find biomarkers associated with the treatment response to antifibrotic agents [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Lara et al obtained evidence that SP-A can downregulate DNA synthesis and inhibit the secretion of inflammatory mediators [44]. The cohort trial performed in Japan in 2020 has shown the efficacy of pirfenidone in IPF based on the reduction of serum concentration of SP-D, concluding that this biomarker might have a predictive and informative value [45].…”
Section: Surfactant Proteins a And D (Sp-a Sp-d)mentioning
confidence: 99%
“…Assassi and colleagues recently developed a prediction model for response to cyclophosphamide and mycophenolate in SSc-ILD using interferon-induced serum proteins ( 172 ). Ikeda et al showed plasma SP-D concentration may predict favorable response to pirfenidone ( 173 ) in patients with IPF, though Neighbors and colleagues showed consistent pirfenidone treatment effect irrespective of plasma concentration for a panel of prospectively collected candidate biomarkers ( 126 ).…”
Section: Peripheral Blood Biomarkersmentioning
confidence: 99%